Cytokinins and auxins control the expression of a gene in Nicotiana plumbaginifolia cells by feedback regulation. - Dominov, J A (1992)
Both cytokinin (N6-benzyladenine [BA]) and auxin (2,4-dichlorophenoxyacetic acid [2,4-D]) stimulate the accumulation of an mRNA, represented by the cDNA pLS216, in Nicotiana plumbaginifolia suspension culture cells. The kinetics of RNA accumulation were different for the two hormones; however, the response to both was transient, and the magnitude of the response was dose dependent. Runoff transcription experiments demonstrated that the transient appearance of the RNA could be accounted for by feedback regulation of transcription and not by the induction of an RNA degradation system. The feedback mechanism appeared to desensitize the cells to further exposure of the hormone. In particular, cells became refractory to the subsequent addition of 2,4-D after the initial RNA accumulation response subsided. A very different response was observed when the second hormone was added to cells that had been desensitized to the first hormone. Under such conditions, BA produced a heightened response in cells desensitized to 2,4-D and vice versa. These findings support a model in which cytokinin further enhances the auxin response or prevents its feedback inhibition. The hormone-induced RNA accumulation was blocked by the protein kinase inhibitor staurosporin. On the other hand, the protein phosphatase inhibitor okadaic acid stimulated expression, and, in particular, okadaic acid was able to stimulate RNA accumulation in cells desensitized to auxin. This suggests that hormone activation involves phosphorylation of critical proteins on the hormone signaling pathway, whereas feedback inhibition may involve dephosphorylation of these proteins. The sequence of pLS216 is similar to genes in other plants that are stimulated by multiple agonists such as auxins, elicitors, and heavy metals, and to the gene encoding the stringent starvation protein in Escherichia coli. It is proposed that this gene family in various plants be called multiple stimulus response (msr) genes.